A Reexamination of the Non-Dischargeability of Criminal Restitutive Obligations in Chapter 13 Bankruptcies - Haberfelde, Ann (1992)
In 1990, the Supreme Court held that criminal restitution was dischargeable as a debt in a Chapter 13 bankruptcy proceeding. Congress subsequently amended the bankruptcy laws to exclude criminal restitution from the debts dischargeable in Chapter 13 proceedings. This amendment represents the elevation of the states' interest in their criminal laws at the expense of the policies served by the bankruptcy laws. By tracing the origins of criminal restitution as a form of punishment, examining the development of bankruptcy discharge policy, and considering the interrelation of state and federal laws, this Note proposes a more equitable solution. Rather than viewing the conflict between the aims of the states' criminal laws and the aims of the federal bankruptcy laws as irreconcilable, this Note suggests the use of a conditional discharge so that both aims can be served